2008
DOI: 10.1364/oe.16.006877
|View full text |Cite
|
Sign up to set email alerts
|

Continuously rotating chiral liquid crystal droplets in a linearly polarized laser trap

Abstract: The transfer of optical angular momentum to birefringent particles via circularly polarized light is common. We report here on the unexpected, continuous rotation of chiral nematic liquid crystal droplets in a linearly polarized optical trap. The rotation is non-uniform, occurs over a timescale of seconds, and is observed only for very specific droplet sizes. Synchronized vertical motion of the droplet occurs during the rotation. The motion is the result of photo-induced molecular reorganization, providing a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…Yang et al reported that continuous rotation of chiral nematic LC droplets is driven by a linearly polarized light [10]. Another alternative strategy is to use micro-objects that can scatter light in a helical manner [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al reported that continuous rotation of chiral nematic LC droplets is driven by a linearly polarized light [10]. Another alternative strategy is to use micro-objects that can scatter light in a helical manner [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We used photopolymerizable LC materials instead of genuine LC droplets and fabricated microgears of various shapes using two-photon microstereolithography. Our aim was to demonstrate the precise switching control of LC microgears compared with previously reported microrotors [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…From quantum mechanics, CP light with angular frequency o carries both linear momentum (LM), :o/c, and SAM, s ± :, per photon with s þ ¼ þ 1 or s À ¼ À 1 for left-or right-handed CP, respectively 14 . The development of optical tweezers 15 (OT) stimulated the exploitation of optical forces and torques in several diverse areas such as biophysics 16 , nanotechnology 13 , complex fluids [17][18][19][20][21] , microrheology 10,11 and microfluidics 22,23 . In particular, several methods have been used to induce optically controlled rotations and alignment: anisotropic scattering due to particle shape 24,25 , form birefringence of anisotropic objects [26][27][28] , optical birefringence 9,12,29 and transfer of angular momentum (AM) from laser beams carrying SAM and/or orbital angular momentum 12,30,31 .…”
mentioning
confidence: 99%
“…We optically trap spherical, non-absorbing, spherulite-like solid microparticles obtained by photopolymerization of cholesteric liquid crystal (CLC) droplets 34 . In contrast to non-polymerized CLC droplets 17,18,20,21 , which present significant complications due to the interaction of a strong light field with the structure of the CLC inside the droplet (for example, director distortions), the solid state of our microparticles is the key enabling feature for the observation of chiral optomechanics. Having a shell structure of refractive index connected to the helicoidal supramolecular architecture, they exhibit a selective Bragg phenomenon that makes them behave as omnidirectional chiral spherical reflectors.…”
mentioning
confidence: 99%
“…Indeed, such prototypical chiral systems have stimulated a significant interest in the context of optical manipulation during the last decade [11][12][13] and, recently, the idea that the polarization state of light can be used as a control parameter for mechanical actions has emerged. Namely, polarization-controlled attractive-repulsive dynamics 14,15 and polarization-controlled optical radiation pressure 16 have been experimentally demonstrated.…”
mentioning
confidence: 99%